2013
DOI: 10.1371/journal.pone.0078670
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Serum Retinol Binding Protein 4 with Atherogenic Dyslipidemia in Morbid Obese Patients

Abstract: Retinol binding protein 4 (RBP4) is an adipokine that may contribute to the development of insulin resistance. However, how this adipokine is affected and its possible involvement in lipid metabolism in obese patients with varying degrees of insulin resistance is yet to be determined. A total of 299 middle-aged morbid obese patients (BMI>40 kg/m2) were divided in euglycemic, metabolic syndrome or type 2 diabetic. Anthropometric measurements, biochemical variables and systemic RBP4 levels were determined. RBP4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…We have previously published evidence that, in insulin resistant states, an increase in fasting triglycerides is associated with a higher percentage of VLDL, which results in smaller, denser LDL particles [14,15]. The atherogenic potential of small and dense LDL particles has been demonstrated in numerous studies [16,17].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We have previously published evidence that, in insulin resistant states, an increase in fasting triglycerides is associated with a higher percentage of VLDL, which results in smaller, denser LDL particles [14,15]. The atherogenic potential of small and dense LDL particles has been demonstrated in numerous studies [16,17].…”
Section: Discussionmentioning
confidence: 98%
“…In any case, none of these studies has evaluated the effect of inositols on postprandial glycaemic response, lipoprotein profile or LDL particle size in healthy subjects under free-living conditions. We have previously published evidence of an increase in small and dense LDL particles in subjects with insulin resistance [14,15] that correlated with the progression of atherosclerosis and earlier and more severe cardiovascular disease [16,17]. Therefore, the primary aim of the present study was to assess the chronic consumption of an oral nutritive inositol-enriched beverage (IEB) on glycaemia (in fasting and postprandial states), insulin levels and insulin resistance.…”
Section: Introductionmentioning
confidence: 97%
“…It has been shown that RBP4 is upregulated in insulin‐resistant conditions associated with obesity and provokes IR by interfering with insulin receptor substrate 1 (Gerrits et al., ; Yang et al., ). In addition, it seems to be a predictor of cardiovascular disease (Alkharfy, Al‐Daghri, Vanhoutte, Krishnaswamy, & Xu, ) and development of atherosclerosis, as it promotes atherogenic dyslipidaemia (Rocha et al., ) and is involved in the regulation of hypertension (Kraus et al., ). Recently, it has been established that RBP4 levels in gingival crevicular fluid and serum are positively correlated with body mass index (BMI) and periodontal parameters (Kanoriya, Pradeep, Mallika, Singhal, & Garg, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that RBP4 is upregulated in insulin-resistant conditions associated with obesity and provokes IR by interfering with insulin receptor substrate 1 (Gerrits et al, 2012;Yang et al, 2005). In addition, it seems to be a predictor of cardiovascular disease (Alkharfy, Al-Daghri, Vanhoutte, Krishnaswamy, & Xu, 2012) and development of atherosclerosis, as it promotes atherogenic dyslipidaemia (Rocha et al, 2013) and is involved in the regulation of hypertension (Kraus et al, 2015).…”
mentioning
confidence: 99%
“…Although central vaspin administration led to reduced food intake [82,88], the mechanism of action remains unclear. Bluher [89] suggested that vaspin inhibited proteases that degrade molecules with glucose lowering effects as well as anti-orexigenic factors.…”
Section: Vaspinmentioning
confidence: 99%